NF‐κB activation in astrocytes drives a stage‐specific beneficial neuroimmunological response in ALS. (6th June 2018) - Ouali Alami, Najwa; Schurr, Christine; Olde Heuvel, Florian; Tang, Linyun; Li, Qian; Tasdogan, Alpaslan; Kimbara, Atsushi; Nettekoven, Matthias; Ottaviani, Giorgio; Raposo, Catarina; Röver, Stephan; Rogers‐Evans, Mark; et al.
Abstract: Astrocytes are involved in non‐cell‐autonomous pathogenic cascades in amyotrophic lateral sclerosis (ALS); however, their role is still debated. We show that astrocytic NF‐κB activation drives microglial proliferation and leukocyte infiltration in the SOD1 (G93A) ALS model. This response prolongs the presymptomatic phase, delaying muscle denervation and decreasing disease burden, but turns detrimental in the symptomatic phase, accelerating disease progression. The transition corresponds to a shift in the microglial phenotype showing two effects that can be dissociated by temporally controlling NF‐κB activation. While NF‐κB activation in astrocytes induced a Wnt‐dependent microglial proliferation in the presymptomatic phase with neuroprotective effects on motoneurons, in later stage, astrocyte NF‐κB‐dependent microglial activation caused an accelerated disease progression. Notably, suppression of the early microglial response by CB2 R agonists had acute detrimental effects. These data identify astrocytes as important regulators of microglia expansion and immune response. Therefore, stage‐dependent microglia modulation may be an effective therapeutic strategy in ALS. Synopsis: Astrocytes influence the course of ALS in a non‐cell‐autonomous manner. Conditional modulation of NF‐κB in astrocytes reveals an unexpected mechanism of astrocyte‐mediated microglia proliferation depending on paracrine Wnt signaling that results in stage‐specific disease modulation. IKK/NF‐κB activation in spinal cord astrocytes triggers proliferation of TMEM119 + microglia cells. Astrocyte‐mediated microglia expansion depends on paracrine Wnt signaling. Biological outcome of amplified microglia is programmed by the pathogenic stage of ALS. Temporal‐restricted astrocytic NF‐κB activation in the presymptomatic phase of ALS promotes beneficial microglia activation and delays disease progression. Stage‐dependent modulation of microglia activation by CB2 R inverse agonists may be a promising therapeutic strategy in ALS. Abstract : Conditional modulation of NF‐κB in astrocytes reveals astrocyte‐mediated microglia proliferation depending on paracrine Wnt signaling that results in stage‐specific disease modulation.